PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN TEKA-TEKI SILANG PADA MATA PELAJARAN SEJARAH KELAS X IPA SMA N 8 KOTA JAMBI - Mohammad Andi Wasgito, Nada tismaliya sari, (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2020)
AbstractThis research and development departs from the problems that occur in SMA N 8 in the city of Jambi where the learning is monotonous and less varied so that students get bored quickly. Learning media can be an alternative in solving problems that occur. This research aims to produce instructional media products, namely crossword puzzles and apply it to history lessons in class X IPA at SMA N 8, Jambi city. The research method used in this research is ADDIE developed by Lee and Owen which has five stages, namely; 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. In the implementation stage, the researcher adopted the Martin Tessmen model. The research was conducted at SMA N 8 Kota Jambi with research subjects of class X IPA students, amounting to 2 people for individual trials, 10 people for small group trials, and 34 people for large group trials. From the results of field trials, it was found that the results of individual trials, the total score an average percentage of 82.6% were included in the "good" category. The results of the small group skoe trial average percentage of 86.8% were included in the "very good" category, the results of the field test results for the average score of 90.74% were included in the "very good" category. For the use of learning media, this crossword puzzle is applied in learning history.Keywords: Media, learning, crossword puzzles AbstrakPeneltian dan pengembangan ini berangkat dari permasalahan yang terjadi di SMA N 8 kota jambi dimana pembelajaran yang dilakukan monoton dan kurang bervariasi sehingga siswa cepat bosan. Media pembelajaran dapat menjadi alternative dalam pemecahan masalah yang terjadi. Penelitian ini bertujaun untuk menghasilkan produk media pembelajaran yaitu teka-teki silang dan menerapkannya pada pelajaran sejarah kelas X IPA di SMA N 8 kota jambi. Metode penelitian yang digunakan dalam penelitian ini adalah ADDIE yang dikembangkan oleh Lee and owen yang memiliki lima tahap yaitu; 1) analisis,2) desain,3) pengembangan,4) implementasi, dan 5) evaluasi. Pada tahap implenrasi peneliti mengadopsi model martin tessmen. Penelitian dilakukan di SMA N 8 kota jambi denagn subjek penelitian siswa kelas X IPA yang berjumlah 2 orang untuk uji coba perorangan, 10 orang untuk uji coba kelompok kecil, dan 34 orang pada uji coba kelompok beasr. Dari hasil uji coba lapangan didapatkan hasil uji coba perorangan, jumlah skor rata-rata persentase 82,6% termasuk kedalam kategori “baik”. Hasil uji coba small group skoe rata-rata persentase 86,8% termasuk kedalam kategori “sangat baik”, hasil uji coba field tes skor rata-rata persentase 90,74% termasuk kedalam kategori “sangat baik”. Untuk penggunaan media pembelajaran teka-teki silang ini diterapkan dalam pembelajaran sejarah.Kata kunci: Media, pembelajaran,  teka-teki silang